2015
DOI: 10.1371/journal.pntd.0004177
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Owned, Free-Roaming Dogs: Implications for Rabies Control

Abstract: BackgroundRabies is a serious yet neglected public health threat in resource-limited communities in Africa, where the virus is maintained in populations of owned, free-roaming domestic dogs. Rabies elimination can be achieved through the mass vaccination of dogs, but maintaining the critical threshold of vaccination coverage for herd immunity in these populations is hampered by their rapid turnover. Knowledge of the population dynamics of free-roaming dog populations can inform effective planning and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
87
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 34 publications
10
87
1
Order By: Relevance
“…Empirical studies showed that canine rabies can be eliminated if 60-80% of the dog population is vaccinated (Cleaveland et al, 2003;Totton et al, 2010). This is in line with theoretical models that estimate that 70% vaccination coverage of a dog population is sufficient to eliminate rabies (Coleman and Dye, 1996;Totton et al, 2010) and this is the vaccination coverage recommended by the WHO (WHO, 2013), although this can be hard to obtain (Conan et al, 2015;Minyoo et al, 2015). This target is based on models that usually assume linear density-dependent disease transmission.…”
Section: Introductionsupporting
confidence: 52%
“…Empirical studies showed that canine rabies can be eliminated if 60-80% of the dog population is vaccinated (Cleaveland et al, 2003;Totton et al, 2010). This is in line with theoretical models that estimate that 70% vaccination coverage of a dog population is sufficient to eliminate rabies (Coleman and Dye, 1996;Totton et al, 2010) and this is the vaccination coverage recommended by the WHO (WHO, 2013), although this can be hard to obtain (Conan et al, 2015;Minyoo et al, 2015). This target is based on models that usually assume linear density-dependent disease transmission.…”
Section: Introductionsupporting
confidence: 52%
“…Preference for male dogs has been reported in some studies [17,37,42,62], because of the belief that male dogs make better guard dogs [29]. A similar study of free-roaming dogs in South Africa, however, reported male-biased sex ratio, even though females did not have higher mortality during one of the study years [68] and a study of dogs in an urban center of central Tanzania found no differences in survival rates between sexes [69]. Lactating females had lower BCS than non-lactating females, suggesting that reproduction has costs.…”
Section: Discussionmentioning
confidence: 91%
“…Acosta-Jamett et al found that although only 28% of dogs were vaccinated against canine distemper (rabies was not mentioned in this study), the mortality rate of adult dogs was 0.2 or less and the main two causes of death were human activities (41%) followed by disease (35%) [42]. Conan et al found that rabies vaccination only reduced mortality rates in unvaccinated puppies and argued that this was highly unlikely due to reduced risk of succumbing to rabies [68]. …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Zoonotic diseases such as rabies, tuberculosis, and brucellosis continue to pose a threat to public health in many parts of South Africa, including the Mnisi study area (Marcotty et al, 2009;Conan et al, 2015). Few households reported a history of an illness that could be linked to animals; however, zoonoses are likely underdiagnosed and misinterpreted in this community (Quan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%